Aspectos éticos de la eutanasia - Rivera López, Eduardo (Análisis Filosófico, 1997)
I analyze sorne traditional distinctions around euthanasia. In contrast to those who most discuss the justification of active versus passive, or direct versus indirect euthanasia, I claim, following and expanding a Holly Smith's argument, that the possibility of active and/or direct euthanasia cannot be morally excluded, once we have accepted passive and/or indirect euthanasia, even though we assume the asymmetry between killing and letting die, or between killing someone intentionally as a means and doing that as an undesired side-effect (the "doctrine ofthe double effect"). I evaluate then some objections and limits ofthe argument and make a shorter reference to the problem of voluntariness.